(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-1-118-130 Abstract. The relevance of the study is due to the fact that in recent years human relation with information flows have changed. The thinking and perception of meanings, especially by the younger generation, also begin to change noticeably. In this regard, the communication of an individual with a literary text presented in digital format deserves more attention. The purpose of the study is to create a model of learning to read this type of text, taking into account the features of a literary hypertext, which will optimize the process of learning to read a literary text in a foreign language. As an example of methodical processing of an autonomous educational hypertext, an excerpt from the story "Scar" by E. Grishkovets was used. In the process of developing a model for teaching foreigners to read literary hypertext, the following methods were used: analytical (linguocultural and linguocognitive analysis), interpretation method and modeling. In the study were compared such concepts as “literary text”, “hypertext”, “electronic hypertext” and “educational fiction text”. Literary hypertext is a traditional text, but it is organized in a different way than a linear text, so when it is perceived, specific perception mechanisms operate. The definition of educational literary hypertext in the aspect of teaching Russian as a foreign language is given; the linguodidactic potential of hypertext in relation to the teaching of Russian as a foreign language is revealed, the algorithm for working with Russian-language literary hypertext in a foreign audience is substantiated. It is assumed that educational hypertext as a new way of artistic communication can exist in two forms: network hypertext and autonomous hypertext. It is concluded that a methodically processed literary text, presented as a hypertext, makes it possible to optimize the process of teaching foreign students to read literary works in Russian. The prospects for the study are seen in the creation of an electronic manual for teaching foreign students to read the works of Russian writers based on the proposed model. Key words: fiction text, hypertext, teaching to read, cognitive aspect, perception, comprehension, task system, Russian as a foreign language (RFL)